Evaluation of customer satisfaction and behaviour intension using expectation confirmation theory: a study of home cooked food in North India / Suvidha Khanna, Sheetal Bhagat and Priyanka Sharma - Khanna, Suvidha; Bhagat, Sheetal; Sharma, Priyanka (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Food technology developments are indicating a shift toward more sustainable and personalized food options. Since 2017, the food industry has been experimenting with home-cooked meals. In the pandemic period, thousands of covid patients are confined at home at that time home prepared meals are in high demand. The present study is to attempt the impact of food quality (FQ), price fairness (PF) and service quality (SQ) on Customer satisfaction (CS). Furthermore, the study also examined the impact of customer satisfaction on behavior intention. Data was collected from customers specifically who had experience with home-cooked food through food delivery services in North India (Delhi, Chandigarh and Jammu & Kashmir). The sample respondents were 335. PLS Structural equation modelling has been used to test the relationship between the constructs. The study proposed a model based on several hypothetical relationships which were derived from the extensive review of the literature. The proposed model is then tested empirically, which reflects the influence of FQ, PF, and SQ; on CS and further, the influence of CS on BI in the selected Home Cooked food Suppliers.